Expand 5(y + 2) using the distributive property

11 answers

To expand \( 5(y + 2) \) using the distributive property, you multiply the 5 by each term inside the parentheses:

\[ 5(y + 2) = 5 \cdot y + 5 \cdot 2 \]

Now, calculate each multiplication:

\[ 5 \cdot y = 5y \] \[ 5 \cdot 2 = 10 \]

Putting it all together, the expanded form is:

\[ 5(y + 2) = 5y + 10 \]

Expand −5(−3 − 11g)

To expand \(-5(-3 - 11g)\) using the distributive property, multiply \(-5\) by each term inside the parentheses:

\[ -5(-3 - 11g) = -5 \cdot (-3) + (-5) \cdot (-11g) \]

Now, calculate each multiplication:

\[ -5 \cdot (-3) = 15 \] \[ -5 \cdot (-11g) = 55g \]

Putting it all together, the expanded form is:

\[ -5(-3 - 11g) = 15 + 55g \]

Is it a negative

Let's clarify the expansion of \(-5(-3 - 11g)\).

Using the distributive property, we have:

\[ -5(-3 - 11g) = -5 \cdot (-3) + (-5) \cdot (-11g) \]

Calculating each term:

  1. \(-5 \cdot (-3) = 15\)
  2. \(-5 \cdot (-11g) = 55g\)

So, combining those results gives:

\[ -5(-3 - 11g) = 15 + 55g \]

There are no negative signs in the final result. The answer is indeed positive:

\[ 15 + 55g \]

If you were asking specifically about any negatives, the expressions involved in the multiplication were initially negatives, but the result from multiplying two negative numbers is positive. If you have any specific conditions or further clarifications, feel free to ask!

Expand 13(q−6) using the Distributive Property.(1

To expand \( 13(q - 6) \) using the distributive property, you multiply \( 13 \) by each term inside the parentheses:

\[ 13(q - 6) = 13 \cdot q + 13 \cdot (-6) \]

Now, calculate each multiplication:

\[ 13 \cdot q = 13q \] \[ 13 \cdot (-6) = -78 \]

Putting it all together, the expanded form is:

\[ 13(q - 6) = 13q - 78 \]

Expand 13(q−6) using the Distributive Property

To expand \( 13(q - 6) \) using the distributive property, you will multiply \( 13 \) by each term inside the parentheses:

\[ 13(q - 6) = 13 \cdot q + 13 \cdot (-6) \]

Now, calculate each multiplication:

  1. \( 13 \cdot q = 13q \)
  2. \( 13 \cdot (-6) = -78 \)

Putting it all together, the expanded form is:

\[ 13(q - 6) = 13q - 78 \]

Expand 1/3(q−6) using the Distributive Property.

To expand \(\frac{1}{3}(q - 6)\) using the distributive property, you will multiply \(\frac{1}{3}\) by each term inside the parentheses:

\[ \frac{1}{3}(q - 6) = \frac{1}{3} \cdot q + \frac{1}{3} \cdot (-6) \]

Now, calculate each multiplication:

  1. \(\frac{1}{3} \cdot q = \frac{1}{3}q\)
  2. \(\frac{1}{3} \cdot (-6) = -\frac{6}{3} = -2\)

Putting it all together, the expanded form is:

\[ \frac{1}{3}(q - 6) = \frac{1}{3}q - 2 \]